10.1016/s0029-7437(08)70707-9 (CrossRef Listing of Deleted DOIs, 2000)
AIM: To describe age-specific clinical features and identify predictors of length of hospital stay in children and adolescents with primary Epstein-Barr virus (EBV) infectious mononucleosis (IM). METHODS: This multicentre retrospective cohort study included all children and adolescents aged 0-17 years with a verified primary EBV infection in the Central Denmark Region between March 2020 and March 2025. RESULTS: Among 1657 serologically verified primary EBV infections, 307 patients (18.5%) required EBV-related hospitalisation. Hospitalisation incidence increased with age. Although adolescents accounted for most EBV-related admissions (77.5%), EBV-infected children below 7 years were hospitalised more often (one in four) than children aged 7 years or older (one in seven). The most common presenting symptoms were tonsillitis (77%), fever (75%) and lymphadenopathy (64%). Hepatic dysfunction was frequent, particularly among adolescents, whereas anaemia and hyperbilirubinemia occurred more often in younger children. Prolonged length-of-stay was independently associated with hyperbilirubinemia, elevated C-reactive protein, organomegaly and secondary bacterial infection. CONCLUSION: Disease severity in paediatric EBV infection was associated with inflammatory and hepatic complications rather than age. Early identification of these features may support risk stratification and optimise inpatient care.